Abū Manṣūr al-Tha᾽ālibī Kitāb Khāṣṣ al-Khāṣṣ - Orfali, Bilal; Baalbaki, Ramzi (Bibliotheca Islamica, 2021)
Muḥammad b. Ismāʿīl al-Thaʿālibī was a poet, critic, lexicographer, historian of literature, prolific scholar, and one of the most important literary figures in the tenth-eleventh centuries. This work of his entitled Khāṣṣ al-khāṣṣ fī l-amthāl is a collection of proverbs and their equivalents in a number of cultures and professions.